Study of the Provision and Utilization of Shared Space in the Taman Royal Housing Complex, Tangerang City - Mochamad Aldi Lutpiana (SM Institute, 2023)
Formal housing (planned settlement) is a housing built by clear rules and equipped with services and completeness of settlements designed before being occupied so that housing has a regular pattern. The availability of shared facilities in a residential area has an important role for the development of housing residents' activities. In the Neighborhood Unit concept, it is explained that the availability of social facilities in housing serves to increase the desire to interact with its inhabitants. The problem that arises now is the availability of shared facilities that are not in accordance with the needs of its users, resulting in low utilization of facilities. The study was conducted to assess the supply, utilization, and knowing the perceptions of occupants regarding the priority of shared facilities needs in Taman Royal Housing, Tangerang City. The study of the provision and utilization of shared facilities is carried out using three research variables, namely the availability, location and intensity of utilization variables. The study used quantitative descriptive analysis method. Meet the study as follows: 1) the availability of shared facilities that are most in accordance with the regulations on urban housing planning in urban areas are worship facilities. 2) facilities that have the lowest utilization rate are health facilities, this is due to poor quality of service. 3) the facilities that are most needed based on residents' perceptions are playing facilities.